The Emerging Role of Intelligence in the World of the Future - Robert J. Sternberg (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [During the 20th century, the world experienced an unprecedented rise in people's cognitive abilities. IQs increased 30 points (with the average IQ remaining 100 only because publishers reset the "average" on their tests). Yet, society's ability to confront serious problems in the world seems as challenged as ever. Problems such as air pollution, global climate change, increasing disparity of incomes, disputes that never seem to move toward resolution (such as between the Israelis and Palestinians), and increasing antibiotic resistance-all of these and many other problems seem to defy us, despite our elevated IQs. Why are there so many serious problems still confronting the world? Why is IQ insufficient for solving serious problems where differences in people's interests are at stake? How can intelligence, broadly defined, help us to create a better world and solve the seemingly intractable problems the world confronts? The essays in this book address these questions and provide some directions for answers.